The effect of the serotherapy regimen used and the marrow cell dose received on rejection, graft-versus-host disease and outcome following unrelated donor bone marrow transplantation for leukaemia. - Byrne, J; Stainer, C; Cull, G; Haynes, A; Bessell, E; Hale, G; Waldmann, H; Russell, N (2000)
Unrelated donor (UD) transplantation is the only potentially curative therapy for many leukaemia patients but is associated with a high mortality and morbidity. We sought to identify factors that could be optimised to improve outcome following UD transplantation in adults. Data was retrospectively analysed on 55 patients sequentially receiving UD transplants for CML or acute leukaemia (AL), all of whom received serotherapy for the prevention of GVHD and rejection. All patients received standard conditioning regimens. The first 28 patients transplanted also received combined pre- and post-transplant serotherapy with Campath 1G (days -5 to +5) and standard dose CsA plus MTX as GVHD prophylaxis (protocol 1). The subsequent 27 patients received a 5-day course of pre-transplant serotherapy alone either with ATG (CML patients) or Campath 1G (AL patients) on days -5 to -1 inclusive, with high-dose CSA plus MTX (protocol 2). The incidence of acute GVHD was low with no patient receiving either protocol developing > grade 2 disease. The use of protocol 2 and the administration of a bone marrow cell dose above the median (2.17 x 10(8)/kg) were the most important factors predicting engraftment (P = 0.03 and P = 0.001, respectively) but this only remained significant for cell dose in multivariate analysis (P = 0.03). Overall survival for the group was 45% at 3 years and was influenced by both age (P = 0.02) and disease status at transplantation (P = 0.001). Receiving a cell dose above the median was also associated with a trend towards better survival (P = 0.08), due primarily to a reduction in the TRM to 8.2% compared with 54.5% in those receiving a lower cell dose (P = 0.002). We conclude that pre-transplant serotherapy alone is highly effective at preventing acute GVHD following UD BMT and that additional post-transplant serotherapy does not confer any benefit. Furthermore, a high marrow cell dose infused has a major effect in reducing transplant related mortality following UD BMT.